Rumen-Degradable Starch Improves Rumen Fermentation, Function, and Growth Performance by Altering Bacteria and Its Metabolome in Sheep Fed Alfalfa Hay or Silage - Wenliang Guo; Meila Na; Shuwei Liu; Kenan Li; Haidong Du; Jing Zhang; Renhua Na (Animals)
Alfalfa silage due to its high protein can lead to easier feeding management, but its high proportion of rumen-degradable protein can reduce rumen nitrogen utilization. Nevertheless, increasing dietary energy can enhance ruminal microbial protein synthesis. Thirty-two Suffolk female sheep were used in this study, with a 2 × 2 factorial arrangement of treatment. The four treatments were a combination of two forage types (alfalfa hay; AH vs. alfalfa silage; AS) and two rumen-degradable starch levels (low RDS; LR vs. high RDS; HR) with a 15 d adaptation and 60 d experimental period. The rumen content and rumen epithelium samples were collected after slaughter. Feeding AS increased the rumen isobutyrate, valerate, ammonia-N (NH3-N) concentration, urase activity, and papillae height (p < 0.05) and reduced the feed to gain (F:G), rumen bacterial protein (BCP), rumen lactic acid concentration, and papillae width (p < 0.05) of sheep. Increased RDS in the diet improved the daily matter intake, average daily gain, and rumen weight, reduced the F:G, and enhanced the rumen nitrogen capture rate by decreasing total amino acids and the NH3-N concentration to increase BCP, aquaporins 3 gene, and protein expression. The rumen microbiota also changed as the HR diet reduced the Chao index (p < 0.05). The metabolomics analysis showed that feeding AS upregulated the rumen tryptophan metabolism and steroid hormone biosynthesis, while the purine metabolism, linoleic acid metabolism, and amino acid biosynthesis were downregulated. Furthermore, increased RDS in the diet upregulated rumen lysine degradation and sphingolipid metabolism, while aromatic amino acid biosynthesis was downregulated. Additionally, the correlation analysis results showed that ADG was positively correlated with 5-aminopentanoic acid, and three microorganisms (unclassified_f__Selenomonadaceae, Quinella, Christensenellaceae_R-7_group) were positively correlated with the rumen isobutyrate, valerate, NH3-N concentration, urase activity, tryptophan metabolism, and steroid hormone biosynthesis and negatively correlated with linoleic acid metabolism and amino acid biosynthesis in sheep. In summary, increased RDS in the diet improved the growth performance and rumen N utilization and reduced bacterial diversity in sheep. The alfalfa silage diet only increased feed efficiency; it did not affect growth performance. Additionally, it decreased rumen nitrogen utilization, linoleic acid, and amino acid biosynthesis. Nevertheless, there were limited interactions between forage and RDS; increased RDS in the AS diet enhanced the nitrogen capture rate of rumen microorganisms for alfalfa silage, with only slight improvements in the purine metabolism, linoleic acid, and amino acid synthesis.